PERENCANAAN DESAIN PARKIR RUMAH SAKIT PENDIDIKAN DENGAN MENGGUNAKAN PROPORSI KENDARAAN (STUDI KASUS :RSGM UDAYANA) - I Made Kariyana kariyana; Tri Hayatining Pamungkas; Ni Made Ola Ulandari (JMTS: Jurnal Mitra Teknik Sipil, 2023)
The need for health services is increasing, influencing the development of the hospital industry and education in the health sector, such as teaching hospitals. In establishing a teaching hospital, a plan is needed, one of which is the provision of parking facilities. RSGM Udayana is a new building, of course it needs parking planning so that during operation there are no parking problems. The purpose of this study was to determine the parking characteristics of the existing lecture building, the value of the parking space unit (SRP) that must be provided at the Udayana General Hospital building and the parking design that can be applied to that location. The parking design at the Udayana General Hospital uses references to the 1998 Land Transportation Directorate Regulations and survei data of existing lecture locations. The results in study are that there are no parking problems at the existing lecture location at Udayana Hospital with the highest parking index for motorbikes 0,58 and cars 0,61, the SRP value applied to the parking layout of RSGM Udayana, namely 160 motorcycles and 76 vehicles, parking design that planned for the Udayana RSGM Building to be divided into 6 (six) zones. Abstrak Kebutuhan akan pelayanan kesehatan semakin meningkat mempengaruhi perkembangan industri rumah sakit dan pendidikan dalam bidang kesehatan seperti rumah sakit pendidikan. Dalam pendirian rumah sakit pendidikan perlu suatu perencanaan salah satunya penyediaan fasilitas parkir. RSGM Udayana merupakan gedung baru tentu perlu perencanaan parkir agar saat beroprasi tidak terjadi permasalahn parkir. Penelitian ini bertujuan yaitu mendapatkan nilai karakteristik parkir gedung perkuliahan eksisting, nilai satuan ruang parkir (SRP) yang harus disediakan pada gedung RSGM Udayana dan desain parkir yang dapat di terapkan pada lokasi tersebut. Pendesainan parkir di RSGM Udayana ini menggunakan acuan Peraturan Direktorat Perhubungan Darat Tahun 1998 dan data survei lokasi perkuliahan eksisting. Hasil penelitian ini yaitu tidak terdapat permasalah parkir pada lokasi perkuliahan eksisting di RSPTN Udayana dengan indeks parkir tertinggi untuk sepeda motor 0,58 dan mobil 0,61, nilai SRP yang diterapkan pada layout parkir RSGM Udayana yaitu sepeda motor 160 dan mobil 76 kend, desain parkir yang direncanakan pada Gedung RSGM Udayana dipecah berdasarkan 6 (enam) zone.